Memperkuat Integrasi Nasional Dengan Memanfaatkan Generasi Muda dan Teknologi Pada Pembelajaran Pendidikan Kewarganegaraan - Rifqi Ghaida Sakhi; Fatma Ulfatun Najicha (FKIP, Universitas Palangka Raya, 2023)
Integration is a process that has been going on since ancient times until now. This process has important continuities and has a significant impact on humans and society as a whole. This article aims to assess whether a sense of nationalism still exists in today's generation. The method used is a qualitative study based on literature studies with data collection from relevant journals with the title